La diète de l'Allemagne du Nord. 'Le Capital' (1866-1867) - Marx, Karl; Engels, Friedrich (Paris : Alfred Costes, 1934)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: Marx, Karl; Engels, Friedrich; Duitsland